2019
DOI: 10.1016/j.ijsolstr.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Expansion modelling based on cracking induced by the formation of new phases in concrete

Abstract: Unexpected expansion can be a cause of damage in quasi-brittle materials such as concrete, fired clays or rocks. Such expansions can be due to chemical reactions (alkalisilica reaction-ASR, sulfate attack) or physical phenomena (frost, transport of fluids). Expansion is caused by two main mechanisms: matrix deformation due to the pressure initiated by the formation of new phases in the porosity of the material, and matrix cracking, which increases the apparent swelling of the matrix. In this work, a poromechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 71 publications
(146 reference statements)
0
7
0
Order By: Relevance
“…Considering the actual working conditions, the two-way coupling method of CFD-DEM is used to simulate the transport process of gas and solid phases in the shot blasting machine recovery unit 38 . Based on the above controlling equations for the gas and discrete phases, the momentum value transmitted from the gas phase to the discrete phase is solved by calculating the momentum change of the particles when they pass through a defined spatial region in the flow field, thus realizing the two-way coupling calculation 39 , 40 .…”
Section: Mathematical Descriptionmentioning
confidence: 99%
“…Considering the actual working conditions, the two-way coupling method of CFD-DEM is used to simulate the transport process of gas and solid phases in the shot blasting machine recovery unit 38 . Based on the above controlling equations for the gas and discrete phases, the momentum value transmitted from the gas phase to the discrete phase is solved by calculating the momentum change of the particles when they pass through a defined spatial region in the flow field, thus realizing the two-way coupling calculation 39 , 40 .…”
Section: Mathematical Descriptionmentioning
confidence: 99%
“…However, the model took diffusion coefficient as a constant and neglected the time-dependent property of a diffusion coefficient. Multon et al [18] proposed a porous medium mechanical model to describe the expansion behavior of concrete materials under sulfate attack and evaluated the opening degree of local cracks under erosion combined with damage mechanics. Islam et al [19] established a diffusion coefficient expression of sulfate related to humidity and temperature and proposed a comprehensive model considering the coupling effect of temperature and humidity on sulfate attack.…”
Section: State Of the Artmentioning
confidence: 99%
“…[1][2][3] Horizontal movable shot blasting machine can realize automatic recovery of shot, but in actual production and processing, it is difficult to recover the waste produced after shot blasting, and the dust particles generated during the recovery process are easy to cause environmental pollution, and the constructor is easy to cause lung disease due to inhalation of large amount of dust. 4 Studies have shown that when the efficiency of waste recovery reaches 95%, it is a relatively efficient and environmental friendly recovery efficiency. In addition, when the degree of shot recycling is low, problems such as long cleaning time 5 and bad effect 6 causing serious damage to shield plate 7 are likely to occur due to insufficient shot.…”
Section: Introductionmentioning
confidence: 99%